UV Spectrophotometric Analysis of Miconazole Nitrate and Eugenol in Topical Formulation - Zanwar, Aarti S. (Asian Journal of Pharmaceutics (AJP), 2023)
Fungal infection remains a continuous and growing threat to human health. Combination therapy may be an optional approach for the treatment of invasive fungal infections, and the potential antifungal mechanisms provide new insights into novel antifungal drug development. Several papers have proven that blend of miconazole nitrate and eugenol has synergistic antifungal effect. Therefore, a formulation used eugenol to increase the skin penetration and increase the availability of miconazole nitrate in topical gels. As a result, a method for simultaneous measurement of the aforementioned medicines in the formulation of emulgel has been devised and validated using UV spectrophotometric analysis. Materials and Methods: In the simultaneous equation method, absorbance was measured at 272 and 280 nm for the estimation of both drugs. Miconazole nitrate and eugenol were estimated at 281 and 271 nm in the first derivative (zero crossing) method, respectively. The ratio derivative method utilized peak amplitudes at 283 and 274 nm for miconazole nitrate and 286 and 292 nm for eugenol. The developed methods were validated according to the ICH guidelines, including parameters such as specificity, linearity, range, precision, accuracy, limit of detection, and limit of quantification. Results and Discussion: All three assay methods showed a direct relationship between response and concentration in the concentration range of 100– 600 μg/mL for miconazole nitrate and 53–318 μg/mL for eugenol. The level of dispersion was within 2% of the RSD. Recovery studies for both drugs ranged from 97 to 102%, recommending that the methods are effective. Conclusion: All of the proposed techniques were found to be quick, accurate, and inexpensive. As a result, they can now be helpful for routine quality control analysis when calculating miconazole nitrate and eugenol in emulgel formulation or formulations containing the aforementioned medications.